Efektivitas Model Tanggap Dalam Meningkatkan Kualitas Pembelajaran PPKN Di Sekolah Dasar - Rabiatul Adawiah; Wahdah Refia Rafianti (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
In elementary schools, civic education (PPKn) is still predominantly centered on traditional teacher-centered approaches. These approaches do not actively engage students and do not help them develop critical thinking skills.  This study tested the TANGGAP learning model, which integrates three approaches: Problem Based Learning (PBL), Numbered Head Together (NHT), and Talking Stick, to improve student activity, critical thinking skills, and learning outcomes. The study was conducted in two cycles on 17 students in fourth grade at SDN Kebun Bunga 3 Banjarmasin. Rubric evaluasi critical thinking, observation sheets for student and teacher activities, and learning outcome tests. Using descriptive quantitative analysis, the data were analyzed to determine the percentage increase for each indicator. The results showed that the TANGGAP model is effective in raising the quality of civics learning in elementary schools by encouraging students to actively participate, work together, and mastery their material. The increase in student activity was 41% to 94%, critical thinking skills was 35% to 88%, and learning mastery was 47% to 94%.